Pengaruh Dosis Dolomit dan Pupuk NPK terhadap Pertumbuhan dan Hasil Sorgum pada Tanah Gambut (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2025)
Sorghum (Sorghum bicolor L.) is an annual crop that is tolerant to drought and requires relatively low water input, making it suitable for cultivation on suboptimal lands such as peat soils. However, the utilization of peat soils for crop production faces major constraints, including high soil acidity and low availability of essential macronutrients, particularly nitrogen (N), phosphorus (P), and potassium (K). Improving the chemical properties of peat soils can be achieved through the application of dolomite to reduce soil acidity and NPK fertilizer to enhance nutrient availability. This study aimed to evaluate the growth and yield responses of sorghum to different combinations of dolomite and NPK fertilizer rates on peat soil and to determine the most efficient dosage. The experiment was conducted using a factorial randomized block design with two factors, namely dolomite rate and NPK fertilizer rate. Observations were made on growth and yield parameters of sorghum. The results showed that the interaction between dolomite and NPK fertilizer had no significant effect on all observed parameters. Based on efficiency analysis, the application of 1.16 kg dolomite per bed and 200 kg NPK per hectare was identified as the most efficient dosage to support the growth and yield of sorghum on peat soil. These findings indicate that appropriate soil amendment and fertilization management are essential for optimizing sorghum production on peat soils.